A critical overview of Ali Shariati's comment on the Islamic Economy - Hasan Kazak; Orhan Çeker (Universitas Negeri Surabaya, 2022)
Islam introduces a system that encompasses and concerns all areas of human life, and the economic structure, which occupies an important place and significance in this human life, is a crucial part of this system. Based on their considerations of the Qur'an and hadith sources, Islamic scholars have classified the five essentials to be protected in Islam: religion, life, mind, generation, and property (six with the addition of